Statistical characteristics of finger-tapping data in Huntington's disease. - Antoniades, C; Ober, J; Hicks, S; Siuda, G; Carpenter, R; Kennard, C; Nemeth, A (2012)
Measuring the rate of finger tapping is a technique commonly used as an indicator of impairment in degenerative neurological conditions, such as Huntington's disease. The information it provides can be greatly enhanced by analysing not simply the overall tapping rate, but also the statistical characteristics of the individual times between each successive response. Recent technological improvements in the recording equipment allow the responses to be analysed extremely quickly, and permit modification of the task in the interest of greater clinical specificity. Here we illustrate its use with some pilot data from a group of manifest HD patients and age-matched controls. Even in this small cohort, differences in the responses are apparent that appear to relate to the severity of the disease as measured by conventional behavioural tests.